Pengaruh Komposisi Kompos Baglog Terhadap Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) - Burhan, Badri; Proyogo, Riski (Politeknik Negeri Lampung., 2018)
Onions are commodities that have high economic value. Demand for shallots continues to increase along with population growth. The use of appropriate planting media will determine growth and yield. In general, a good growing media is a medium of fertile soil, rich in organic matter, availability of nutrients in sufficient quantities, and the ratio of air and water contained in it is balanced. The purpose of this study was to determine the effect of doses of baglog compost (oyster mushroom waste) on the growth and production of shallots. The research was carried out in polybags in the Bandar Lampung experimental plot. The 4-month research period starts from November 2016 to February 2017. The research method used a Randomized Block Design (RBDD) with five replications. The composition of baglog compost with volume consists of six levels: K0 = control treatment; K1 = ground: baglog (3: 1); K2 = land: baglog (2: 1); K3 = ground: baglog (1: 1); K4 = land: baglog (1: 2); and K5 = ground: baglog (1: 3). Research results: (a). Application of compost doses on soil treatment of 50%: baglog 50% has a significant effect on higher growth and production, namely on variable plant height = 53.57 cm; number of tubers = 5.40 pieces; tuber weight = 31.53 grams; and tuber diameter = 2.05 cm. While the application of baglog compost with a composition of 67% of land: 33% of baglog gives a real effect on the variable number of leaves is greater as many as 13 strands, and the wet weight of onion is 48.10 grams. Composition of baglog soil compost 33%: baglog 67% and soil 25%: baglog 75% shows low parameter results. In the treatment of 33% of land: 67% compost bagasse and 25% soil: baglog compost 75%) the intensity of fusarium wilt attacks reached 14.67%, and 35%. The greater the amount of baglog given to the planting media allows the growing media to store more water and the higher soil moisture.